A TiO2/PEO composite incorporated with in situ synthesized hyper-branched poly(amine-ester) and its application as a polymer electrolyte. Issue 86 (2nd September 2016) - Hou, Gao-Ming; Zhang, Ming-Qiu; Huang, Yi-Fu; Ruan, Wen-Hong
Abstract : By in situ synthesizing hyper-branched poly(amine-ester) in TiO2 /PEO nanocomposite, efficient ion transporting among the nano inclusions can be obtained. Abstract : This paper has reported a new polymer nanocomposite of nano-titanium dioxide/polyethylene oxide (TiO2 /PEO) incorporated with in situ synthesized hyper-branched poly(amine-ester) (HBPAE) and its application as a polymer electrolyte. Firstly, the HBPAE/HBPAE- g -TiO2 /PEO is obtained by synthesizing HBPAE in methyl acrylic acid methyl ester grafted TiO2 (MMA- g -TiO2 )/PEO, to simultaneously form the hypergrafted polymer on the nano inclusions (HBPAE- g -TiO2 ) and hyperbranched particles dispersed in the PEO. Then the Li2 SO4 is introduced to prepare the polymer electrolyte, and the relevant structure and properties are studied. It is found that the incorporation of HBPAE into TiO2 /PEO can benefit the ionic transportation of the composite electrolyte, and can bridge the nano inclusions which further improves ionic conductivity. The best ionic conductivity of the HBPAE/HBPAE- g -TiO2 /PEO polymer electrolyte with 15 wt% TiO2 content can reach as high as 3.2 mS cm −1, which is ∼10 times of that of the PEO electrolyte and ∼28% of that of the HBPAE- g -TiO2 /PEO electrolyte without homopolymer component. Furthermore, the optimized polymer electrolyte is assembled into a LiTi2 (PO4 )3 //LiMn2 O4 lithium-ion battery, with better excellent cell performance compared with the PEO electrolyte. This study shows that the new polymer nanocomposite has great potential for the assembly of high performance solid electrochemical devices.